Exercise in the management of hypertension: A case report - Cruz-Ferreira, António (2013)
Physical inactivity is a problem in modern society and its association with hypertension and other cardiovascular diseases is well known. In treating diseases associated with environmental risk factors, the prescription of regular exercise is a tool that can be used by family physicians. We report the case of a 60-year-old sedentary woman who came to her family doctor after measuring elevated blood pressure at home. An individual treatment program was prescribed, consisting of lifestyle changes and promotion of regular aerobic exercise. After 6 months of treatment, the patient had normal blood pressure values and no anti-hypertensive drugs were required. We want to encourage family physicians to prescribe regular aerobic exercise as a first line or adjuvant treatment in hypertensive patients.